Activated carbons from the Amazonian biomass andiroba shells applied as a CO2 adsorbent and a cheap semiconductor material. (August 2022) - Serafin, Jarosław; Ouzzine, Mohammed; Xing, Congcong; El Ouahabi, Hajar; Kamińska, Adrianna; Sreńscek-Nazzal, Joanna
Abstract: Amazonian andiroba shell was used as a non-expensive, renewable biomass resource to produce a porous activated carbon as a CO2 adsorbent and a cheap supercapacitor material. Activated carbons were prepared by CO2 physical activation of hydrochars obtained from hydrothermal carbon of biomass. The effect of activation times (1 h, 5 h, and 10 h) at 880 ºC on the physical characteristics of the activated carbons was investigated. A significant increase of surface area (from 616 to 1937 m 2 /g) with respect to the activation time was observed. AC-AND-5 h showed good microporosity, with the highest adsorption capacity of CO2 was obtained as 3.2 mmol/g and 6.1 mmol/g at 25 ºC and 0 ºC up to 1 bar, respectively. The sample AND-AC-5 h shows a good CO2 /N2 selectivity and fast adsorption kinetics that be easily regenerated with superior cyclic stability after multiple cycles. Moreover, it proved that the photogenerated electrons and holes in wide band gap carbon can be easily transferred into carbon, resulting in a suppressed charge recombination. The best charge transfer processes was received for AC-AND-1 h sample. Graphical Abstract: ga1 Highlights: Activated carbons were prepared with HTC method successfully. The textural properties can be tailored by the time carbonization. The CO2 uptake reached up to 6.1 mmol/g and 3.2 mmol/g at 0 and 25 ºC, respectively. AC-AND-5 h sorbent had highly stable after 15 consecutive adsorption-desorption cycles. AC-AND-1 h had the best steady-state charge transfer process